A field study of the effect of humor in print advertising on diffusion of the advertising message - Bir, Ali Atıf (Marquette University, 1990)
A field experiment was used to measure the effect of humor in print advertising on diffusion of the ad message. Three versions of the same advertising message were created. Two of the advertisements differed in terms of the integration of humor with the major selling point of the ad. The third one communicated the message without any funny item. The advertisements were sent out to sixty-five randomly selected student subjects, split into the three different groups. The subjects who received the humorous ad in which humor is unrelated to the main selling point were distracted by the unrelated humor. The recall of the main selling point was high when the humorous ads in which humor is related to the main selling point and the serious ads were received. High recall of the main selling point did not yield to the higher diffusion of the main selling point.
Sadece dijital ortamda erişilebilir.
Keywords: Mizah, Reklamlarda